Fabrication of novel polyurethane matrix-based functional composites with enhanced mechanical performance - Anum Yaseen; Muhammad Umair; Z.A. Rehan; Layla A. Alahmari; Eman Fayad (Results in Engineering)
Thermoplastic polyurethane (TPU) has gained significant interest in several fields, including automobile steering wheels, and the electronics sector due to their easier processability, abrasive resistance, and self-lubricating performances. However, their strong inherent flammability and significant smoke and heat production during burning limit their industrial applications. Therefore, its applicability can be enhanced with the addition of high-strength reinforcement and making them antibacterial and flame-retardant. This research is designed to examine the influence of zirconium phosphate (ZrP) and zinc oxide (ZnO) nanoparticles on the novel polyurethane/glass fiber reinforced composites for flame retardant and antibacterial applications with improved mechanical performance. Three different types of novel polyurethane (PU1, PU2, PU3) matrices were prepared using different recipes, and 7 % ZrP and 5 % ZnO nanoparticles were added to the polyurethane matrices separately, and their corresponding composite samples were fabricated using glass reinforcement. Mechanical i.e., Charpy impact, hardness and tensile, and functional i.e., flame retardancy (FR) and antibacterial tests were performed to compare their performance. Mechanical testing results showed that PU3-based composite samples showed the highest values of impact force, hardness, and tensile strength in both ZrP and ZnO nanoparticle-based composite samples. Furthermore, 7 % ZrP-PU3 composite exhibited the best performance of flame retardancy due to the presence of hexamethylene diisocyanates (HDI) content. Likewise, the 5 % ZnO-PU3-based composite exhibited the highest antibacterial activity along with enhanced mechanical performance.